Nursing Management Strategies for a Patient With an Aeson CARMAT® Total Artificial Heart: a Case Report - Simone Amato; Giulia Fattore; Andrea Battisti; Valentina De Bartolo; Vincenza Giordano; Niccolò Simonelli; Anna Rita Marucci; Francesco Gravante (Infermieristica Journal, 2025)
Introduction. Total artificial heart (TAH) devices are a viable bridge to transplantation in patients with end-stage biventricular heart failure. Among these, the Aeson CARMAT® TAH offers pulsatile flow and biocompatible materials to enhance physiological compatibility and reduce thromboembolic risks.